DYNAMICS OF THE MICROARTHROPOD’S GUILDS UNDER LARETIA ACAULIS (Acta Entomológica Chilena, 2022)
The micro-arlhropod fauna from soil and inner spaces of the cushion-lorm plants oí Laretia acaulis isanalyzed in this paper. The sampling was carried out monthly along the whole sampling period of ninemonlhs. in the localily of La Parva in the Andes near Santiago (Región Metropolitana), at 2.640 m alt..and when there was not snow cover.The micro-Arlhropods were extracted by means of Berlese-Tullgren funnels and each samplc was250 cc. in volunte.The taxonomic analysis of higher taxa, ntostly of miles (Acari) and Colleinbolan inseets is hereinpresented, the reponed laxa representing funclíonal guilds.The distribution of densities is recorded for each taxon, and correlations among the recordeddensily and soil water contení, temperalure, soil pH, organic matter, soluble N - P - K concentration. arealso labulated.Significant correlations were found for sonte of lite higher taxa and the organic matter contení, thesoluble N and K, parlicularly the lalter which correlales well with the densities of Oribatids. Tarsonemidsand Gamasids.The most frequenl group with Itigh densities all along the research period was Actinedida(Prostigmata).Comparison between soil samples with and without vegetation shows a faunal-concentrating effectfor the Laretia cushions.
Keywords: Microarthropods. Guilds. Annual eyele. High allitude. Laretia acaules